Prevalence and Associated Risk Factors of Gastrointestinal Parasite Infections among Meat Goats in Khon Kaen Thailand - Sarinya Rerkyusuke; Sawarin Lerk-u-suke; Raktham Mektrirat; Anuwat Wiratsudakul; Prapan Kanjampa; Saikam Chaimongkol; Nattaya Phanmanee; Miranda Visuddhangkoon; Panicha Pattayawongdecha; Nanticha Piyapattanakon; Pongpatchara Krajaipan; Pitchapa Sutamwirat (Veterinary Medicine International)
This study investigated the epidemiology of gastrointestinal (GI) parasite infections among 42 meat goat herds in Khon Kaen, Northeast Thailand, based on 913 fecal samples. The predominant parasites identified in the herd were strongyle (100.0%, 42/42), Trichuris spp. (73.8%, 31/42), Eimeria spp. (66.7%, 28/42), Moniezia spp. (64.3%, 27/42), Strongyloides spp. (38.1%, 16/42), and Paramphistomum spp. (7.1%, 3/42). Coinfection with at least two GI parasites was observed in 90.4% of the herds. Molecular analysis confirmed Haemonchus contortus and Trichostrongylus spp. as the strongyle species. The study explored parasite prevalence among animals, finding significant correlations with season, sex, age, and breed. Notably, the wet season showed increased strongyle and Eimeria spp. infections. Female animals had higher odds of strongyle infection, while younger animals (less than 1 year) were more susceptible. Conversely, animals aged over 1 year were more likely to be positive for Trichuris spp., Moniezia spp., and Eimeria spp. infections. Female animals exhibited poor body condition scores (BCS) and anemia, as indicated by the FAMACHA score and packed cell volume (PCV) levels. Correlations between age, clinical signs, hematological parameters, biochemistry, and GI parasite burdens were investigated, revealing significant associations. These findings emphasize the need for tailored intervention strategies considering seasonal variations, age, and sex differences for effective GI parasite control in meat goats. Prioritizing animals exhibiting poor BCS and elevated FAMACHA score is imperative to mitigate the deleterious impacts of GI parasitic infections on health and productivity.